Tourism Sector Development and Economic Growth in OIC Countries - Uula, Mimma Maripatul; Maulida, Syahdatul; Rusydiana, Aam Slamet (SMART Insight, 2023)
This study aims to examine the impact of the tourism sector on economic growth in 53 OIC member countries. This study uses 4 independent variables namely population, open trade, inflation, and international tourism receipts. The data used is annual panel data from 2010 to 2021, obtained from SESRIC OIC. The analysis method applied in this study is static panel data regression. The results showed that all independent variables, such as population, open trade, inflation, and international tourism receipts, have a significant influence both simultaneously and partially on the economic growth variable (GDP). The tourism sector stimulates other industries through direct, indirect, and induced impacts, contributes to job creation, and causes positive economies of scale. In addition, investments in the tourism sector can positively impact tourism performance indicators such as travel and tourism GDP, international tourism receipts, and international tourist arrivals.